Cytotoxic selectivity of MJCO.3 and MJCo.s, acidic ribosome-inactivating proteins isolated from Mirabilis jalapa L. leaves against various cancer cell-lines - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
ABSTRACT Mirabilis jalapa L. contains basic (MJ30) and acidic (MJC) Ribosome-inactivating proteins (RIPsl. Further purification of MJC has been found two RIPs, MJCO.3and MJCo... This study is aimed to prove the cytotoxic selectivity of MJCo.3andMJCo..against many cancer cell-lines and normal cell line. The two RIPs,MJCo.3andMJCo.. were tested their cytotoxic effect on 8 human cancer cell lines and normal cell using MTT assay compared with MJC protein. The highest cytotoxic activities of MJCO.3and MJCo.. were against EVSA-T followed by T47D, HeLa, WiDR, SiHa, Raji, NS1, and MCF7, with the IC.oof 59.3,102.4,162.9,190.5,249.5, and 304.5I!g/mL, respectively for MJCO.3and 32.8, 75.5, 86.0,108.3,346.7, and 220.06I!g/mL, respectively for MJCo... Based on these IC.o values, MJCO.3and MJCo.. were specific to EVSA-T and T47D, whereas they were not selective against Raji and SiHa (SI< 10.0). It can be concluded that he acidic RIPs isolated from M. jalapa L. leaves was potential to be developed as anticancer agents for breast cancer. Key words: acidic RIPs - M. jalapa L.- cytotoxic selectivity - cancer eel/lines.